Molecular and biological analysis of the putative golgi mannosidase II and other enzymes involved in N-linked glycosation in drosophila melanogaster - Lockyer, A; Lockyer, Anne (1995)
﻿ Glycosylation is a fundamental post-translational modification of proteins that occurs in all eukaryotes, but the biological significance of specific glycosylation structures is still largely unknown. We have chosen to study this process by cloning and characterizing the genes involved in the N-linked glycosylation pathway in Drosophila melanogaster and analysing mutants of these genes. Since this biochemical pathway for the production of N-linked glycans is considerably conserved, studying it in Drosophila, a useful organism for genetic research, should yield results applicable to other eukaryotes. This thesis describes the attempt to identify a Drosophila homologue of rat ER mannosidase and how this investigation resulted in the identification of a Drosophila cDNA with considerable homology to calnexin, an enzyme involved in the folding of N-glycosylated proteins. It also describes the cloning and characterization of the genomic sequence for the putative Golgi mannosidase II (GmII)* in Drosophila. The expression and control of expression of GmII have been investigated further, and have suggested expression of this gene throughout Drosophila development. Analysis of the GmII promoter region has shown expression from a TATA-less promoter contained within 288bp of sequence 5' to the start of transcription.